Pengaruh Media Boneka Tangan Terhadap Kemampuan Mengendalikan Emosi Anak Kelompok B Di RA Al Almourky Kecamatan Telaga Kabupaten Gorontalo - Mbayang, Wahyuningsih; Puspa Ardini, Pupung; Sutisna , Icam (Efektor, 2023)
Emotional control ability is the ability of an individual to be aware of and control their emotions, both positive and negative, in order to direct them towards appropriate actions. The purpose of this study is to determine whether there is an influence of hand puppet media on the emotional control ability of children at Raudhatul Athfal Almourky. This study is an experimental study with a One Group Pre-Test Post-Test Design. The population in this study was 124 children. The sample for this study consisted of 20 children from class B2. The results of the study show that the Pre-Test data had an average of 15.4 and a standard deviation of 2.458. Meanwhile, the Post-Test data obtained an average of 28.75 and a standard deviation of 3.462. This indicates that the average scores of the respondents tested in this study increased from the initial test to the final test. The calculated t-value was 2.411, with a t-table of 2.093. This means that hand puppet media has an influence on the emotional control ability of children. This study confirms that hand puppet media can be applied as a learning medium that can control the emotional ability of children.